Letters from Tom Hales to Florence O'Donoghue regarding injuries and torture Hales received during the Irish War of Independence - Hales, Thomas, 1892-1966; O'Donoghue, Florence, 1895-1967 (1924)
Includes copy statement with preface titled 'Torture of Tom Hales and Pat Harte'.
Keywords: Hales, Thomas, -- 1892-1966; Harte, Patrick, -- -1924; Irish Republican Army; Great Britain. -- Army -- Ireland -- History -- 20th century; Ireland -- History -- War of Independence, 1919-1921